Lentinus saisamorniae (Polyporaceae, Polyporales), a new edible macrofungus from northern Thailand - Kumla, Jaturong; Kaewnunta, Atsadawut; Suwannarach, Nakarin (Phytotaxa, 2025)
A new edible Lentinus species, described herein as L. saisamorniae, was collected from local markets and natural habitats in northern Thailand between 2019 and 2021. This species is characterized by its small to medium-sized basidiomata, white to yellowish-white pileus, broadly ellipsoid to elongate-shaped basidiospores, dimitic hyphal system, and hyphal pegs. Nonetheless, its longer basidia and smaller basidiospores make it distinguishable from L. cladopus. A molecular phylogenetic analysis of the combined internal transcribed spacer (ITS) large subunit (nrLSU) of nuclear ribosomal DNA, and RNA polymerase II large subunit (rpb1) sequences supported the monophyly of L. saisamorniae as a distinct lineage within the genus Lentinus. Therefore, this new species was introduced based on both morphological characteristics and molecular phylogeny. A full description, illustrations, color photographs, and a phylogenetic tree to show the placement of L. saisamorniae are provided. Comparisons between the new species and morphologically similar and related species are discussed.